Housing Loans: What About Personality Traits? - Gambetti, Elisa; Giusberti, Fiorella (International Journal of Economics and Financial Issues, 2017)
To investigate the role of personality traits (16PF model) on psychological attitudes about mortgage behaviour, 263 participants were asked their preferences and perceptions about housing loans. Results showed that: extraversion positively predicted the preference for housing loans with adjustable rates, but also the tendency to change this preference; anxiety negatively predicted the preference for having housing loans, preferring fixed-rate mortgages, and the perception of high risks and low levels of predictability; tough-mindedness was positively associated with a preference for fixed-rate mortgage (maintaining this preference over time), and with the perception over adjustable-rate mortgages of low risks and low predictability; independence negatively predicted the preference for adjustable-rate mortgages. These findings fit with a growing body of evidence suggesting that individual differences influence perceptions and preferences about mortgages. Keywords: Personality; Mortgage; Risk Perception; Preferences. JEL Classifications: E44, G23